Coding Mutations in Vacuolar Protein-Sorting 4 AAA+ ATPase Endosomal Sorting Complexes Required for Transport Protein Homologs Underlie bc-2 and New bc-4 Gene Conferring Resistance to Bean Common Mosaic Virus in Common Bean - Soler-Garzón, Alvaro; McClean, Phillip E.; Miklas, Phillip N. (Frontiers in Plant Science, 2021)
Bean common mosaic virus (BCMV) is a major disease in common bean (Phaseolus vulgaris L.). Host plant resistance is the most effective strategy to minimize crop damage against BCMV and the related Bean common mosaic necrosis virus (BCMNV). To facilitate breeding for resistance, we sought to identify candidate genes and develop markers for the bc-2 gene and the unknown gene with which it interacts. Genome-wide association study (GWAS) of the Durango Diversity Panel (DDP) identified a peak region for bc-2 on chromosome Pv11. Haplotype mapping narrowed the bc-2 genomic interval and identified Phvul.011G092700, a Vps4 AAA+ ATPase ESCRT protein, as the bc-2 candidate gene. The race Durango Phvul.011G092700 gene model, bc-2[UI 111], contains a 10 kb deletion, while the race Mesoamerican bc-2[Robust] consists of a single SNP deletion. Each mutation introduces a premature stop codon, and they exhibit the same interaction to the pathogroups tested. Phvul.005G125100, another Vps4 AAA+ ATPase ESCRT protein, was identified as the candidate gene for the new recessive bc-4 gene, and the recessive allele is likely an amino acid substitution in the MIT domain. The two Vps4 AAA+ ATPase ESCRT proteins exhibit high similarity to the Zym Cucsa.385040 candidate gene associated with recessive resistance to Zucchini yellow mosaic virus in cucumber. bc-2 alone has no resistance effect, but when combined with bc-4, provides resistance to BCMV (except PG-V) but not BCMNV, and when combined with bc-ud, provides resistance to BCMV (except BCMV PG-VII) and BCMNV. So instead of different resistance alleles (i.e., bc-2 and bc-22), there is only bc-2 with a differential reaction based on whether it is combined with bc-4 or bc-ud, which are tightly linked in repulsion. The new tools and enhanced understanding of this host-virus pathogen interaction will facilitate breeding common bean for resistance to BCMV and BCMNV.